Ultratrace Determination of Cr(VI) and Pb(II) by Microsample Injection System Flame Atomic Spectroscopy in Drinking Water and Treated and Untreated Industrial Effluents - Jameel Ahmed Baig; Tasneem Gul Kazi; Latif Elci; Hassan Imran Afridi; Muhammad Irfan Khan; Hafiz Muhammad Naseer (Journal of Analytical Methods in Chemistry)
Simple and robust analytical procedures were developed for hexavalent chromium (Cr(VI)) and lead (Pb(II)) by dispersive liquid-liquid microextraction (DLLME) using microsample injection system coupled with flame atomic absorption spectrophotometry (MIS-FAAS). For the current study, ammonium pyrrolidine dithiocarbamate (APDC), carbon tetrachloride, and ethanol were used as chelating agent, extraction solvent, and disperser solvent, respectively. The effective variables of developed method have been optimized and studied in detail. The limit of detection of Cr(VI) and Pb(II) were 0.037 and 0.054 µg/L, respectively. The enrichment factors in both cases were 400 with 40 mL of initial volumes. The relative standard deviations (RSDs, ) were <4%. The applicability and the accuracy of DLLME were estimated by the analysis of Cr(VI) and Pb(II) in industrial effluent wastewater by standard addition method (recoveries >96%). The proposed method was successfully applied to the determination of Cr(VI) and Pb(II) at ultratrace levels in natural drinking water and industrial effluents wastewater of Denizli. Moreover, the proposed method was compared with the literature reported method.